Sharia Economic Dispute Resolution: Case Study in the Religious Court of JAKPUS Related to Murabahah - Mustofa Mustofa; Ustad Adil (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the resolution of sharia economic disputes in case studies at the Central Jakarta Religious Court regarding Mudharabah. The method used is descriptive qualitative by studying related sources. The results of this research are that resolving sharia economic disputes related to murabahah in the Religious Courts requires a careful approach. The results of this research are that sharia economic dispute resolution provides better legal protection for the parties, and strengthens public trust in the sharia economic justice system. It is proven that the public prefers the Religious Courts which have executorial rights compared to the National Sharia Arbitration Board (BASYARNAS)